Moj obcy kraj? - Rudawski, Michal, 1918- (Warszawa : Agencja Wydawnicza Tu, 1996)
The autobiography of a Polish-Jew, who fought in WW II, and who, because of anti-semitism emigrated to Sweden.
Keywords: Rudawski, Michal, -- 1918-; Poland. -- Wojsko Polskie -- Biography; Jews -- Poland -- Biography